2014
DOI: 10.17265/2159-5542/2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preeclampsia on Perinatal Risks and Infant Temperaments Among Mothers With Antenatal Depression

Abstract: Importance Preeclampsia and depression are two most prevalent disorders known to affect pregnant women and unborn infant. However, few studies have prospectively examined the adverse influence of the in-utero exposures to the two disorders on the optimal development in their offspring, including mortality, adverse birth outcomes, and infant temperament styles. Objectives (1) To examine whether exposures to preeclampsia and antenatal depression were associated with developmental indices of offspring at birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…In a very large-scale study (Bekkhus et al, 2011), child's crying behavior and aggressive behavior were highest if the mother showed high anxiety and depression both during and after pregnancy, while maternal symptoms that lasted during pregnancy only were not associated with child aggressive or crying behavior at age 3 years. Some studies confirm a previous observation (DiPietro et al, 2006) of a positive association between maternal distress in pregnancy and better infant self-regulation (i.e., duration of orientation; Kantonen et al, 2015;Lin et al, 2014), less infant affective reactivity (Rothenberger et al, 2011b), and/or observed that maternal distress is associated with infant positive affectivity (Lin et al, 2014;Nomura et al, 2014) and better social behavior (Lin et al, 2017). However, some studies found no associations between maternal distress during pregnancy and either self-regulation/adaptive functioning (Braeken et al, 2017;Zande and Sebre, 2014) or positive affectivity (Zande and Sebre, 2014) or other aspects of infant temperament (Baibazarova et al, 2013b;Bhat et al, 2015).…”
Section: Caosupporting
confidence: 79%
See 1 more Smart Citation
“…In a very large-scale study (Bekkhus et al, 2011), child's crying behavior and aggressive behavior were highest if the mother showed high anxiety and depression both during and after pregnancy, while maternal symptoms that lasted during pregnancy only were not associated with child aggressive or crying behavior at age 3 years. Some studies confirm a previous observation (DiPietro et al, 2006) of a positive association between maternal distress in pregnancy and better infant self-regulation (i.e., duration of orientation; Kantonen et al, 2015;Lin et al, 2014), less infant affective reactivity (Rothenberger et al, 2011b), and/or observed that maternal distress is associated with infant positive affectivity (Lin et al, 2014;Nomura et al, 2014) and better social behavior (Lin et al, 2017). However, some studies found no associations between maternal distress during pregnancy and either self-regulation/adaptive functioning (Braeken et al, 2017;Zande and Sebre, 2014) or positive affectivity (Zande and Sebre, 2014) or other aspects of infant temperament (Baibazarova et al, 2013b;Bhat et al, 2015).…”
Section: Caosupporting
confidence: 79%
“…Most studies continue their follow-up until the age of six months, while some studies continue the follow-up study until 10 months (Braeken et al, 2013;Peltola et al, 2017;van den Heuvel et al, 2015b), 24 months (Blair et al, 2011;Stroustrup et al, 2016) or 36 months (Bekkhus et al, 2011;Lin et al, 2017;Stroustrup et al, 2016). As was seen in earlier studies (Räikkönen et al, 2011) and regardless of the kind of measurement of temperament or its timing, most evidence points to associations between prenatal stress and high scores on two partially overlapping temperament traits: namely, negative affectivity (sadness, distress to limitations, fear, discomfort, and anger) (Blair et al, 2011;Braithwaite et al, 2013;Green et al, 2016;Hill et al, 2013;Huynh, 2014;Lin et al, 2014;Nomura et al, 2014;Peltola et al, 2017;Pluess et al, 2011;Rouse and Goodman, 2014;van den Heuvel et al, 2015b;Zande and Sebre, 2014) and "difficult temperament" (negative affectivity, intense reactions, slowness in adapting to new situations and irregular routines; Chong et al, 2016;Della Vedova, 2014;Green et al, 2016;Lin et al, 2017;McMahon et al, 2013;Rode and Kiel, 2016;Stroustrup et al, 2016). In a very large-scale study (Bekkhus et al, 2011), child's crying behavior and aggressive behavior were highest if the mother showed high anxiety and depression both during and after pregnancy, while maternal symptoms that lasted during pregnancy only were not associated with child aggressive or crying behavior at age 3 years.…”
Section: Caomentioning
confidence: 95%
“…We therefore meta-analysed unadjusted results. While associations remained after adjustment for baseline confounders in the few studies with adjustments (Erickson, 2018;Nomura et al, 2014Nomura et al, , 2019Spry et al, 2019;Zhang et al, 2017), potential for confounding remains. Thus, we describe meaningful patterns of associations rather than draw causal conclusions (Hernán et al, 2015).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A further possible explanation is confounding. In the few studies with adjusted analyses, associations remained after adjustment for demographic and substance use factors (Erickson, 2018;Nomura et al, 2014Nomura et al, , 2019Spry et al, 2019;Zhang et al, 2017). Nonetheless, potential for confounding remains.…”
Section: Does Timing Of Parent Internalizing Symptoms or Infant Na Mamentioning
confidence: 99%
“…[12] Infants born to preeclamptic mothers were associated with an over fivefold increased risk for infant mortality, a three to sevenfold increased risk for poorer birth outcomes, a three to fivefold increased risk for low birth weight, and compromised neurodevelopmental index. [13] MicroRNAs (miRNAs) are short RNA molecules consisting of 19 to 25 nucleotides in size that control posttranscriptional silencing of the targeting genes. [14] Recent studies suggest that miRNAs are shown to be upregulated in the development of preeclampsia and are suggested to inhibit angiogenesis, trophoblast cells proliferation, placentation and migration.…”
Section: Introductionmentioning
confidence: 99%